RANCANGAN MODEL TURBIN ANGIN BERTINGKAT SUMBU VERTIKAL TIPE CROSSFLOW MENGGUNAKAN COMPUTATIONAL FLUID DYNAMIC (CFD) UNTUK DIAPLIKASIKAN DI JAKARTA - Michael Febrianus Johny Saputra (2020)
In general, wind turbines are divided into 2 types namely, horizontal axis wind turbines and vertical axis wind turbines. One type of vertical axis wind turbine is a crossflow wind turbine. Crossflow turbines are able to work towards low wind direction so as to produce a high torque coefficient. The working principle of crossflow turbines is more widely used for water turbines and includes the type of action turbine (impulse turbine). In this study, crossflow wind turbines have the same geometry as previous studies, but differ in the number of blades or blades, which are 10 pieces, and in this study, modified by making them stratified and will be simulated with wind speeds of 2-4 m / s using Computational Fluid Dynamic software (CFD) with the aim to the extent that cross-level vertical wind turbines can be efficient in low conditions. The result is a vertical axis wind turbine type crossflow type get maximum power coefficient in the number 0.183736458 at TSR 0.3 and wind speed 2m / s. Based on the results it can be concluded that the number of blades greatly influences the difference in results on this crossflow wind turbine with the results of previous studies.